ASTCT Clinical Practice Recommendations for Transplantation and Cellular Therapies in Multiple Myeloma - Dhakal, Binod; Shah, Nina; Kansagra, Ankit; Kumar, Ambuj; Lonial, Sagar; Garfall, Alfred; Cowan, Andrew; Poudyal, Bishesh Sharma; Costello, Caitlin; Gay, Francesca; Cook, Gordon; Quach, Hang; et al. (Transplantation and Cellular Therapy, 2022)
Over the past decade, therapeutic options in multiple myeloma (MM) have changed dramatically. Given the unprecedented efficacy of novel agents, the role of hematopoietic cell transplantation (HCT) in MM remains under scrutiny. Rapid advances in myeloma immunotherapy including the recent approval of chimeric antigen receptor (CAR) T-cell therapy will impact the MM therapeutic landscape. The American Society for Transplantation and Cellular Therapy convened an expert panel to formulate clinical practice recommendations for role, timing, and sequencing of autologous (auto-HCT), allogeneic (allo-HCT) and CAR T-cell therapy for patients with newly diagnosed (NDMM) and relapsed/refractory MM (RRMM). The RAND-modified Delphi method was used to generate consensus statements. Twenty consensus statements were generated. The panel endorsed continued use of auto-HCT consolidation for patients with NDMM as a standard-of-care option, whereas in the front line allo-HCT and CAR-T were not recommended outside the setting of clinical trial. For patients not undergoing auto-HCT upfront, the panel recommended its use in first relapse. Lenalidomide as a single agent was recommended for maintenance especially for standard risk patients. In the RRMM setting, the panel recommended the use of CAR-T in patients with 4 or more prior lines of therapy. The panel encouraged allo-HCT in RRMM setting only in the context of clinical trial. The panel found RAND-modified Delphi methodology effective in providing a formal framework for developing consensus recommendations for the timing and sequence of cellular therapies for MM.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Allogeneic transplantation; Autologous transplantation; CAR T-cells; Cellular therapy; Consensus; Multiple myeloma